2006
DOI: 10.1161/01.res.0000201958.59020.1a
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Cortactin Phosphorylation by Src Contributes to Polymorphonuclear Leukocyte Transmigration In Vitro

Abstract: Abstract-The underlying mechanisms that regulate leukocyte transendothelial migration through the vascular endothelium remain unclear. Cortactin is a substrate of Src tyrosine kinases and a regulator of cytoskeletal dynamics. Previous studies demonstrated a role for Src phosphorylation of cortactin in clustering of E-selectin and intercellular cell adhesion molecule-1 around adherent leukocytes. In the current study, we used an in vitro flow model to investigate the role of Src-induced cortactin phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 32 publications
(59 reference statements)
10
99
0
Order By: Relevance
“…When expressed in cells with endogenous cortactin, this mutant had only a small dominant negative effect, and the mutant protein localized to podosomes, suggesting that the tyrosine residues have a primary or direct role in cortactin function. Consistent with our results, the 3YF cortactin mutant failed to rescue a cortactin knockdown defect in endothelial cells assayed for the ability to support leukocyte transmigration (Yang et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…When expressed in cells with endogenous cortactin, this mutant had only a small dominant negative effect, and the mutant protein localized to podosomes, suggesting that the tyrosine residues have a primary or direct role in cortactin function. Consistent with our results, the 3YF cortactin mutant failed to rescue a cortactin knockdown defect in endothelial cells assayed for the ability to support leukocyte transmigration (Yang et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, PP2 and KI-Src inhibited VSMC migration, indicating that Src kinase activity mediates VSMC migration. Nifedipine potently inhibited PDGF-induced Src activation and tyrosine phosphorylation of Cas, paxillin, and cortactin, all of which have been implicated in cell migration [16][17][18] . Indeed, Kyaw and colleagues reported that Cas is involved in Anginduced VSMC migration 23) , and we previously used RNA interference techniques to demonstrate that Cas, cortactin, and paxillin are required for VSMC migration (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Src phosphorylates several actin-associated proteins, such as Cas, paxillin, and cortactin 14,15) . Tyrosine phosphorylation of these proteins has been reported to be involved in cell migration [16][17][18] . PDGF increased tyrosine phosphorylation of Cas, paxillin, and cortactin, and nifedipine significantly inhibited PDGF-induced phosphorylation of these proteins (Fig.…”
Section: Effect Of Nifedipine On Pdgf-induced Src Activation and Tyromentioning
confidence: 99%
“…Yang et al (22,43) have demonstrated a requirement for Src-mediated phosphorylation of cortactin specifically in paracellular leukocyte TEM. It was also shown that cortactin phosphorylation is required for leukocyte-mediated cytoskeletal remodeling as well as clustering of ICAM-1 (43).…”
Section: Discussionmentioning
confidence: 99%